High-b-value Diffusion-weighted MR Imaging of Suspected Brain Infarction - Meyer, Joel R. (AJNR Am J Neuroradiol, 2000)
BACKGROUND AND PURPOSE: Recent technological advances in MR instrumentation allow acquisition of whole-brain diffusion-weighted MR scans to be obtained with b values greater than 1000. Our purpose was to determine whether high-b-value diffusion-weighted MR imaging improved contrast and detection of signal changes in acute and chronic brain infarction. METHODS: We prospectively evaluated the MR scans of 30 subjects with a history of possible brain infarction on a 1.5-T MR imager with 40 mT/meter gradients (slew rate 150 T/m/s) by use of the following single-shot echo-planar diffusion-weighted MR sequences: 1) 7999/71.4/1 (TR/TE/excitations, b = 1000; 2) 999/ 88.1/3, b = 2500; and 3) 7999/ 92.1/4, b = 3000. Diffusion-weighted MR imaging was performed in three orthogonal directions during all sequences. All subjects were scanned with fast fluid-attenuated inversion recovery (FLAIR) (10,006/145/2200/1 [TR/TE/TI/excitations]) and fast spin-echo T2-weighted (3650/95/3 [TR/TE/excitations], echo train length, 8). The diagnosis of brain infarction was established by clinical criteria. RESULTS: Twenty women and 10 men with a mean age of 67.7 years were enrolled in the study. One subject was excluded owing to poor image quality. Twelve of 29 subjects had a clinical diagnosis of acute infarction. All 12 had lesions that were hyperintense on diffusion-weighted images at all three b values; five were cortical and seven subcortical. There was increased contrast of all lesions on high-b-value scans (b = 2500 and 3000). Lesions that were hypointense on diffusion-weighted images were identified and evaluated at the three different b values. At b = 1000, there were 19 hypointense lesions, whereas at b = 2500 and 3000 there were 48 and 55 lesions, respectively. On FLAIR and T2-weighted images, these low-signal lesions were predominantly chronic, subcortical, ischemic lesions and lacunar infarcts, but four chronic cortical infarcts, one porencephalic cyst, and one primary brain tumor were also found. Low-signal lesions were also noted to have increased contrast on high-b-value diffusion-weighted scans. CONCLUSION: High-b-value diffusion-weighted MR imaging (b = 2500 or b = 3000) had no impact on diagnosis of acute infarction. High-b-value diffusion-weighted MR imaging (b = 2500) combined with diffusion-weighted MR imaging at b = 1000 improves tissue characterization by increasing the spectrum of observed imaging abnormalities in patients with suspected brain infarction.